The effects of artificial aging on high translucent zirconia. Issue 1 (20th December 2019) - Kou, Wen; Garbrielsson, Klas; Borhani, Adrian; Carlborg, Markus; Molin Thorén, Margareta
Abstract: Zirconia is known for its high strength but lacking translucency. Recently, a new type of high translucent zirconia, 5 mol% yttria partially stabilized zirconia (5Y-PSZ), with a larger fraction of cubic zirconia phase has become commercially available. However, the resistance to aging of these commercially available zirconia materials is not yet fully established. Purpose: The aim of the present study was to analyze the effects of artificial aging on surface roughness, transparency, phase transformation and biaxial flexural strength of two 5Y-PSZ products, DD cubeX 2 and Prettau Anterior. Materials and methods: The artificial aging was performed in an autoclave under 2 bars of pressure at 134 °C for 10 hours, which is estimated to correspond to 30–40 years in vivo . Artificial aging for 10 hours had no significant effect on surface roughness, transparency, or phase transformation for either of the tested materials. Results: DD cubeX 2 had higher mean flexural strength than Prettau Anterior both before and after artificial aging for 10 hours ( p  < .05). DD cubeX 2 showed, however, a significant reduction in flexural strength after artificial aging ( p  < .05), whereas Prettau Anterior showed a slight increase in flexural strength after artificial aging but not at a significant level. Conclusion: Within the limitation of the present study, both DD cubeX 2 and Prettau Anterior seems to be relatively resistant to aging. However, a wider range of measured flexural strength indicated that Prettau Anterior probably is a less stable material than DD cubeX 2, which also means that the flexural strength of DD cubeX 2 could be more predictable.